Number of berries per m2 for Pinot noir and Chardonnay in Alsace, Bourgogne and Champagne - Eric Duchêne; Dominique Meluc; Laurent Panigai; François Langellier; Christine Monamy; Christophe Schneider (OENO One, 2001)
Yield components leading to the number of berries per m2 were measured for two varieties in Alsace, Burgundy and Champagne, three vineyards in northern France. The number of shoots per m2, the number of inflorescences, the number of flowers and the number of berries per shoot were recorded on the same plots of Pinot noir and Chardonnay between 1995 and 1999. The data showed a great variability of the number of flowers per shoot between years, whereas the number of inflorescences and the number of berries per shoot were more stable. All the yield components, especially the number of flowers per shoot, were lower in Burgundy when compared to Alsace or Champagne. Differences between Pinot noir and Chardonnay are discussed. Fruit set ratio, always above 40 p. cent, are more linked to the number of flowers per shoot than to the number of berries per shoot. A new method for characterising fruit set is proposed.